Classical fragile-X phenotype in a female infant disclosed by comprehensive genomic studies - Paula Jorge; Elsa Garcia; Ana Gonçalves; Isabel Marques; Nuno Maia; Bárbara Rodrigues; Helena Santos; Jacinta Fonseca; Gabriela Soares; Cecília Correia; Margarida Reis-Lima; Vincenzo Cirigliano; et al. (BMC, 2018)
Abstract Background We describe a female infant with Fragile-X syndrome, with a fully expanded FMR1 allele and preferential inactivation of the homologous X-chromosome carrying a de novo deletion. This unusual and rare case demonstrates the importance of a detailed genomic approach, the absence of which could be misguiding, and calls for reflection on the current clinical and diagnostic workup for developmental disabilities. Case presentation We present a female infant, referred for genetic testing due to psychomotor developmental delay without specific dysmorphic features or relevant family history. FMR1 mutation screening revealed a methylated full mutation and a normal but inactive FMR1 allele, which led to further investigation. Complete skewing of X-chromosome inactivation towards the paternally-inherited normal-sized FMR1 allele was found. No pathogenic variants were identified in the XIST promoter. Microarray analysis revealed a 439 kb deletion at Xq28, in a region known to be associated with extreme skewing of X-chromosome inactivation. Conclusions Overall results enable us to conclude that the developmental delay is the cumulative result of a methylated FMR1 full mutation on the active X-chromosome and the inactivation of the other homologue carrying the de novo 439 kb deletion. Our findings should be taken into consideration in future guidelines for the diagnostic workup on the diagnosis of intellectual disabilities, particularly in female infant cases.